Climbing simulated vegetation to heights of ungulate hosts by larvae of Dermacentor albipictus (Acari: Ixodidae) ... - Samuel, W. M.; Shostak, A. W.; McPherson, M. (University of Alberta Library, 2000)
Abstract: Larvae of winter ticks, Dermacentor albipictus (Packard), ascend vegetation in autumn and form clumps that attach to passing ungulate hosts. We tested the hypothesis that vegetation height determines the height of clumps. During the vegetation-to-ungulate transmission period (early September to mid-November), larvae were released. at the base of simulated vegetation (nylon rods 245 cm tall) in outdoor and laboratory trials and in the absence of host cues. Rod height exceeded the height of the tallest ungulate host, which is the moose, Alces alces (L.). Most larvae stopped climbing and formed clumps 50-190 cm above ground, which coincided with torso heights of moose; elk, Cervus elaphus L.; and deer, Odocoileus spp. Rafinesque. More clumps formed in outdoor trials than in laboratory trials and clump heights tended to increase over. the course of the experiment, but clump number, size, and height did not cell-elate with weather conditions. Winter tick larvae appear to determine their height above ...